2023
DOI: 10.1021/acsomega.3c00405
|View full text |Cite
|
Sign up to set email alerts
|

Water Content-Controlled Formation and Transformation of Concomitant Pseudopolymorph Coordination Polymers

Abstract: Two concomitant pseudopolymorph coordination polymers {[Cd2L2(OAc)4]·2DMSO} n (1) and {[CdL(OAc)2]·2.75H2O} n (2) were synthesized by self-assembly of 1,4-bis(4-pyridyl)-2,3-diaza-1,3-butadiene (L) and cadmium acetate in DMSO. Single-crystal X-ray diffraction confirmed that 1D ladder structural motifs exist for pseudopolymorphs 1 and 2 which contain DMSO and water guest molecules, respectively. Our study illustrated the active role of solvent water content in obtaining compound 2. We find that the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…Our structural analysis by the Rietveld method showed that two water molecules replaced coordinated methanol and acetonitrile molecules in 1 and 2 , respectively. A similar humidity-induced structural transformation has recently been reported by us. , …”
Section: Results and Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our structural analysis by the Rietveld method showed that two water molecules replaced coordinated methanol and acetonitrile molecules in 1 and 2 , respectively. A similar humidity-induced structural transformation has recently been reported by us. , …”
Section: Results and Discussionsupporting
confidence: 89%
“…In special cases, this process can lead to chemical bond cleavage and the formation of new bonds for coordinated (solvent) molecules. Therefore, in some reports of single-crystal-to-single-crystal (SCSC) transformation, the change in the coordination environment of the metal can be observed. ,, External stimuli, like humidity, , light, temperature, and mechanical forces can induce a structural transformation process. In particular, the water molecule as a green solvent can not only be added to the compound when crystals are immersed in water, but also participate in this process through the moisture absorbed from the air. ,,, It should be noted that SSST can affect the size of crystals, and in some cases, microcrystalline powder materials are produced (crystal-to-powder transformation). ,,, The significance of water as a source of life on earth and for health development is quite obvious.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though there are various examples of water-induced SCSC transformations reported up to date, this synergistic induction along with ligand-substitution is, however, relatively rare. Most of the water-triggered SCSC transformations involve dehydration/rehydration in which the water molecule played its role as ligand and/or guest molecules. The completion of the 1a → 1b and 2a → 2b SCSC transformations was studied by PXRD (see Figure a,b). In addition, the BET (Brunauer–Emmett–Teller) surface areas of 1a , 1b , 2a , and 2b were determined to be 1.17, 4.70, 2.28, and 4.41 m 2 /g, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%